Tokoh-tokoh Teori Belajar Humanistik dan Urgensinya pada Pembelajaran Pendidikan Agama Islam - Bagus Malik Alindra; Ahmad Makinun Amin (Education Mind Based Development Association, 2021)
Abstract: The objectives of this article is to explain theory of humanism that is a thought was in a way that humanizes humans in their lives. Islam Education Learning as a learning platform has become a space for educators to adopt such a humanistic approach. Learning theorists have tried to give their ideas on such humanistic concepts as Abraham Maslow, Carl R. Rogers, Arthur combs, kolb, honey and Humford and Hebermas. This research employed qualitative methods with an analytic descriptive approach. The type of method employed library research. The results of this article are the concepts pioneered by each character. Abraham Maslow explained the theory of his needs. Carl R Rogers explained the concept of freedom with his principles of study. Meanwhile, Arthur Combs explained the concept of meaningfulness accompanied by an illustration of the concept of a small circle and a large circle. Then, Kolb explained the four stages of learning, as well as Honey Humford and Hebermas explained about several categories of students and the types of learning by students. The concepts of these learning theories have an urgency toward learning, especially on Islamic Education. In this regard, humanistic educators, especially Islamic Education educators are expected to apply these learning theories in Islamic Education learning, so that learners can become humanitarians and behave positively according to the teachings given from the Islamic Education learning process.